Effect Of Fertility Levels And Herbicide Mixtures On Yield And Yield Attributes Of Rainfed Maize Under Temperate Conditions Of Kashmir (Applied Biological Research, 2016)
The present study was aimed to assess the response of rainfed maize to  various fertility levels and weed management practices under temperate  Kashmir conditions. The field experiment consisted of 3 fertility levels of  NPK viz., 60:40:20, 75:50:30 and 90:60:40, N:P2O5:K2O kg ha-1) and 4  weed management practices viz., no weeding, two hand weeding 20 and  50 days after sowing (DAS), atrazine @ 1.0 kg a.i. ha-1 (as pre emergence) + one hand weeding 20 DAS, and atrazine @ 1.0 kg a.i. ha-1 (pre-emergence) + isoprotron @ 1.0 kg a.i. ha-1 (post-emergence). The  results revealed that fertility levels of 90:60:40 and 75:50:30 (NPK) were  at par and showed significant increase in cob length, cobs plant-1, grains  cob-1, 100-seed weight, grain yield, biological yield and stover yield as  against fertility level of 60:40:20 NPK. However, the number of rows  cob-1 and cob diameter showed significant improvement with increase in  fertility level. Increase in fertility level from 60:40:20 to 75:50:30 NPK  significantly enhanced harvest index but further addition caused  significant decrease. Weed management practices of atrazine as pre emergence application + one hand weeding at 20 DAS was at par with  atrazine as pre-emergence + isoprotron as post-emergence application  treatment and both showed significant improvement in all yield  contributing characters over no weeding and 2 hand-weedings at 20 and  50 days DAS. Both grain and stover yields were significantly higher with  atrazine as pre-emergence application + 1 hand weeding at 20 DAS over  hand weeding on 20 and 50 DAS and no weeding.
Keywords: Fertility levels; grain yield; maize; weed management; yield attributes